The Effect of Mind Mapping Learning Method on the Reading Ability of Grade 3 Elementary School Students - Syasmita, Indah; Fauzi; Latifah Annisa; Radianto, Aramiko Agus (Global Action and Education for Society, 2025)
The purpose of this study is to ascertain how reading learning results affect learning outcomes for primary school pupils using mind mapping techniques. One of the linguistic skills that pupils need to develop is reading. In contrast, the mind mapping technique is a method for learning how to use ideas or thoughts in a creative way. By looking at past events, quantitative research employing an ex-post facto methodology is the kind of study that is being conducted. Twenty-five third-graders from SD 101780 Percut Sei Tuan made up the study's sample. Purposive sampling was the method of sampling employed in this investigation. Test methods employing instruments in the form of questions are used to gather data on reading ability learning outcomes. Descriptive analysis is the data analysis method employed to test hypotheses with the aid of the Microsoft Excel application. The following are the findings from this study: 1) Mind mapping approaches for third-grade elementary school pupils have an impact on their reading learning results (sig = 0,017). 2) The experimental class that used mind mapping techniques outperformed the control class in terms of average learning results. Therefore, the findings of this study demonstrate that the mind mapping technique can impact students' learning results in reading.